Plastic limit load and its application to the fracture toughness testing for heterogeneous single edge notch tension specimens. (11th October 2013) - Paredes, M.
ABSTRACT The current investigation pursues the confirmation of the applicability of the limit load solutions in determination of the η factors necessary for fracture toughness testing protocols. The procedure begins with the correct calculation of limit load values in welded single edge notch tension (SE(T)) fracture specimens containing centreline cracks. Hence, the η factor is inferred through the principle of potential energy. Additionally, such results are compared with those obtained from finite element analyses, including strain hardening effects available in the literature. SE(T) specimens subject to pin‐loading display that the η factors are insensitive to the configurational effects and hardening properties. On the other hand, in clamped SE(T) specimens, such effects become meaningful, making its usage in fracture toughness experiments questionable. This work provides an alternative methodology to compute fully plastic proportionality coefficients (η) based on limit load solutions for heterogeneous cracked SE(T) specimens. These analyses also consider the limitations and potentialities of such an approach in experimental measurements of ductile crack growth.